Adipose tissue-derived small extracellular vesicles modulate macrophages to improve the homing of adipocyte precursors and endothelial cells in adipose tissue regeneration - Dong, Jia; Wu, Bin; Tian, Weidong (Frontiers in Cell and Developmental Biology, 2022)
Rapid infiltration of endogenous cells induced by cell-free biomaterials is the first and crucial step in tissue regeneration and macrophage is largely involved. Our previous study reported adipose tissue-derived small extracellular vesicles (sEV-AT) could successfully promote adipose tissue regeneration. However, the role of macrophages in this process was unknown. In this study, we isolated sEV-AT and subcutaneously implanted it into the back of SD rats. The results showed sEV-AT increased macrophage infiltration significantly, which was followed by improving homing of adipocyte precursors (APs) and endothelial cells (ECs). However, when macrophages were depleted by clodronate liposome within 1 week, the homing of APs and ECs, and adipose tissue regeneration were destroyed. In vitro, sEV-AT showed the ability to promote the migration of macrophages directly. Besides, sEV-AT-pretreated macrophages improved the migration of APs and ECs, accompanied by the increase of chemokines (MCP-1, SDF-1, VEGF, and FGF) and the activation of NF-kB signaling pathway. These findings indicated sEV-AT might regulate the secretion of chemokines via activating NF-kB signaling pathway to improve homing of APs and ECs and facilitate adipose tissue regeneration. These findings deepened our understanding of small extracellular vesicle-induced tissue regeneration and laid a theoretical foundation for the clinical application of sEV-AT.